Pelatihan Penggunaan Mendeley dalam Menulis Sitasi dan Daftar Pustaka bagi Mahasiswa Uniflor dalam Penulisan Tugas Akhir - Mei, Maria Fatima; Wondo, Maria Trisna Sero; Sa'o, Sofia; Mei, Agustina; Seto, Stefania Baptis; Ningsih, Ningsih; Naja, Finsensius Yesekiel; Djou, Ana Maria Gadi (LPPM Universitas Flores, 2022)
Readers can verify the information or read more about the topic. The bibliography also allows the author to retrace the steps that have been taken and find information that the author has used for the assignment and find further views or ideas discussed by the author. In fact, students have not been able to use the Mendeley application in writing citations and making a bibliography, whereas nowadays students are required to write articles that will be published in national journals before graduation. Therefore, Mendeley training is needed for fluency in article preparation, because all national journals demand to use of the Mendeley application in citation writing and making a bibliography. The purpose of this training is for students to be able to write good and correct citations and bibliography. Implementation Method The approach method used is direct training on proposals that have been prepared by students who are programming the final project. This training was carried out at the University of Flores for 8th-semester students of the mathematics education study program who programmed their final project. The total number of students who participated in the training was 20 people, requiring participants to bring their own laptops and proposals. The method is used in the form of lectures, practice question sessions, and answers. Participants are enthusiastic and motivated to take part in the training because the knowledge gained from this training will greatly assist participants in writing final assignments and articles. More than 80% of students are able to install applications and plug-in Ms. Word independently. However, some students still have difficulty registering the application using email. Students are expected to carry out continuous exercises so that they can apply Mendeley in the life of the scientific community.